The role of the cognitive peak and its implications for achieving outstanding performanceAnalytical study of the views of a sample of the staff of the University of Baghdad - عبد الرزاق, الاء نبيل (Journal of Economics and Administrative Sciences, 2011)
Knowledge represents the foundation stone for the work of all organizations, are working who leads the thinking of individuals is the ability that leads to behavior based on rationality, it is the work that creates value to the organization and thus gain access to performance winning where that knowledge is a new type of capital based on the thought and experience and is the so-called intellectual capital, which is renewable and is constantly evolving. The study sought to explain the role of the climax  knowledge in achieving the highest levels of performance Organizational and then access to the performance winning in educational organizations the study sample, was found to be a correlation between the climax knowledge cognitive  and performance winning ,Valdhirop knowledge significant effect on performance dimensions winning .